Intrahousehold responses to imbalanced human capital subsidies: Evidence from the Philippine conditional cash transfer program - David A. Raitzer; Odbayar Batmunkh; Damaris Yarcia (Asian Development Bank (ADB), 2021)
Extensive global evidence suggests that conditional cash transfers (CCTs) encourage long-term investment in human capital by poor households. However, CCTs also have the potential to distort incentives for investment among children. If only some children in the household are monitored/subsidized for compliance with conditionalities, returns to household investment in those children increase relative to siblings who are unmonitored/unsubsidized. This paper demonstrates that puzzling nutrition effects of the Philippine CCT are driven by effects on children unmonitored for educational compliance, due to a cap of monitoring at most three children per household. Regression discontinuity design interacted with a secondary instrument for monitoring finds that while monitored children have improved human capital investment, such investment declines for unmonitored children relative to nonbeneficiaries. Patterns are consistent for parental expectations, health, anthropometric, and educational outcomes, and are stronger for boys, in accordance with theoretical expectations. Equalized incentives among children can enhance intended CCT effects.
Keywords: D13; D91; I24; I38; 330; social protection; conditional cash transfer; human capital; intrahousehold allocation